Pharmaceutical Industry - R&D Investment Link to Profitability & Market Value - Vlasatý, Martin; Neumaierová, Inka, 1960-; Hájek, Jiří; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2013)
The aim of this thesis is to examine whether there is a positive relationship between pharmaceutical firms' investments in research and development (R&D) and their profitability as well as market value. This is achieved by employing the simple linear regression analysis, based on sample data gathered over five-year period per each of the fifteen selected leading research-based pharmaceutical companies. The results show that there is statistically significant but relatively weak linear association between level of R&D expenditures and firms' profitability and market value, if measured by Return on Sales, Return on Assets, or Price-to-Sales ratios. Nevertheless, no significant link was identified in case of level of R&D investments and Return on Equity, or Price-to-Book Value ratio. Thus, overall, based on the sample data analyzed, it can be concluded that there is a very limited potential for boosting research-based pharmaceutical firm's profitability as well as market value solely by increasing its R&D expenditures.
Vedoucí práce: Inka Neumaierová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses